As máscaras do feminino em Mário de Sá-Carneiro - Candian, Ronério (2007)
The main objective of this study is to analyze the work A Confissão de Lúcio under the perspective of the Wonderful and Fantastic, as well as the life and the social-political-economic-cultural moment in which the Portuguese author, Mário de Sá-Carneiro, lived, either in Lisbon or in Paris. We consider it relevant to analyze the poet´s life due o the close relationship life-work, which we believe had a strong and peculiar influence, in comparison to other authors of the time. As to the historical moment, we dedicated special attention to a factor which we consider important to complement our study: the 70´s Generation and Orpheo, taking into consideration the objective of each one, the importance of collaborators and the contribution of the creations in the life and culture of the Portuguese people in those times, where the reflex of these changes can be felt until today. Into the study of the narrative, we inserted the study of the double myth and its importance in the work of Mário de Sá-Carneiro, as how Man sees in the other the possibility of completing himself, and, why not, to project in the other what he desires to be or to have. Our views about this are based on the theories of the Collective Unconsciousness and the Dream Analysis by Jung. In this way, as we seek in the narrative the awareness of this myth, we can consider, especially, the characters of Lúcio, Ricardo de Loureiro and his wife Marta, and the enigmatic figure of the American fulva . However, we emphasize that, according to our analysis, the double myth is seen throughout his work. In a subtle approach and in the necessity of a deeper study, we bring to special attention the myth of Salomé-brilliantly depicted by Oscar Wilde and Gustave Flaubert- in the attempt to approximate the character to her dancethe fire orgy and the American fulva and her voluptuous defense as Art